2022
DOI: 10.1101/2022.06.13.22276332
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Atlas of plasma nuclear magnetic resonance biomarkers for health and disease in 118,461 individuals from the UK Biobank

Abstract: Blood lipids and metabolites are both markers of current health and indicators of risk for future disease. Here, we describe plasma nuclear magnetic resonance (NMR) biomarker data for 118,461 participants in the UK Biobank, an open resource for public health research with extensive clinical and genomic data. The biomarkers cover 249 measures of lipoprotein lipids, fatty acids, and small molecules such as amino acids, ketones, and glycolysis metabolites. We provide a systematic atlas of associations of these bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…Presently, NMR metabolic biomarkers have been quantified (Nightingale Health Plc.) and made available through UK Biobank for approximately one third of randomly selected participants ( Methods ) 4 . After sample QC ( Methods ), NMR metabolic biomarker data were available for 121,657 UK Biobank participants: 117,994 at baseline assessment (2006–2010) and 5,139 at first repeat assessment (2012–2013).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Presently, NMR metabolic biomarkers have been quantified (Nightingale Health Plc.) and made available through UK Biobank for approximately one third of randomly selected participants ( Methods ) 4 . After sample QC ( Methods ), NMR metabolic biomarker data were available for 121,657 UK Biobank participants: 117,994 at baseline assessment (2006–2010) and 5,139 at first repeat assessment (2012–2013).…”
Section: Resultsmentioning
confidence: 99%
“…Technical variation is inherent to all laboratory measurements used for molecular phenotyping at biobank scale. Here, we comprehensively explored and document the sources and impacts of technical variation on the NMR metabolite biomarker data that has been made available for ~120,000 UK Biobank participants 4 . We found that the vast majority of biomarkers are relatively robust to technical variation, but that a small subset are significantly impacted by inter-spectrometer variation, within-spectrometer drift over time, and intra-plate variation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Here we leverage the recently published Nightingale NMR data that is now available for ~100,00 participants of the UK Biobank to refine the metabolic architecture of these genetic lipid risk loci with a comprehensive set of 168 metabolite and lipoprotein related traits (Methods and Supplementary Tables 1&2) [18][19][20][21] . We hypothesize that this kind of deep molecular phenotyping will shed new light onto the biological functions of the Graham et al lipid risk genes and their role in regulating lipoprotein composition and turnover.…”
Section: Introductionmentioning
confidence: 99%